Endosome and Golgi‐associated degradation (EGAD) of membrane proteins regulates sphingolipid metabolism. (27th May 2019) - Schmidt, Oliver; Weyer, Yannick; Baumann, Verena; Widerin, Michael A; Eising, Sebastian; Angelova, Mihaela; Schleiffer, Alexander; Kremser, Leopold; Lindner, Herbert; Peter, Matthias; Fröhlich, Florian; Teis, David
Abstract: Cellular homeostasis requires the ubiquitin‐dependent degradation of membrane proteins. This was assumed to be mediated exclusively either by endoplasmic reticulum‐associated degradation (ERAD) or by endosomal sorting complexes required for transport (ESCRT)‐dependent lysosomal degradation. We identified in Saccharomyces cerevisiae an additional pathway that selectively extracts membrane proteins at Golgi and endosomes for degradation by cytosolic proteasomes. One endogenous substrate of this endosome and Golgi‐associated degradation pathway (EGAD) is the ER‐resident membrane protein Orm2, a negative regulator of sphingolipid biosynthesis. Orm2 degradation is initiated by phosphorylation, which triggers its ER export. Once on Golgi and endosomes, Orm2 is poly‐ubiquitinated by the membrane‐embedded "Defective in SREBP cleavage" (Dsc) ubiquitin ligase complex. Cdc48/VCP then extracts ubiquitinated Orm2 from membranes, which is tightly coupled to the proteasomal degradation of Orm2. Thereby, EGAD prevents the accumulation of Orm2 at the ER and in post‐ER compartments and promotes the controlled de‐repression of sphingolipid biosynthesis. Thus, the selective degradation of membrane proteins by EGAD contributes to proteostasis and lipid homeostasis in eukaryotic cells. Synopsis: Ubiquitin‐dependent membrane protein degradation is thought to occur primarily via ERAD or ESCRT pathways. Endosome and Golgi‐associated degradation (EGAD) of membrane proteins from post‐ER compartments represents a novel mechanisms contributing to proteostasis and lipid homeostasis in S. cerevisiae . EGAD selectively extracts membrane proteins from Golgi and endosomes for degradation by cytosolic proteases. Orm2, a repressor of sphingolipid synthesis, represents the first endogenous EGAD substrate. Cdc48/VCP extracts Orm2 from membranes following its ubiquitination by the Dsc ubiquitin ligase complex. EGAD‐dependent Orm2 degradation is essential for a controlled de‐repression of sphingolipid synthesis. Abstract : A novel mechanism for ubiquitin‐dependent extraction from post‐ER compartments regulates proteostasis of yeast membrane protein in addition to ERAD and ESCRT pathways.